Pecuniary returns to working conditions in Viet Nam - Christophe J. Nordman; Smriti Sharma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Using matched worker-firm data from three waves of the Viet Nam Small and Medium Enterprises data, we examine whether workers are compensated with higher wages for working in vulnerable jobs and unfavourable working conditions. Wage equations indicate that there are no clear compensating mechanisms for working in poor conditions, for having an informal contract, and for having few financial benefits. Quantile regressions show that workers in the upper tail of the wage distribution are more likely to be penalized for working in adverse conditions. Employees recruited through official hiring channels with an informal contract earn less than employees hired through social networks. Upon estimating mean decompositions of wage gaps based on working conditions, we find that the gap is almost entirely explained by the conjunction of worker, job and firm characteristics in 2015, in contrast to the previous survey year of 2013.
Keywords: C21; J31; J81; O53; 330; compensating differentials; vulnerability; working conditions; hiring channels; SME; Viet Nam